Diffractive dijet production at HERA - Adloff, C; Anderson, M; Andreev, V; Andrieu, B; Arkadov, V; Arndt, C; Ayyaz, I; Babaev, A; Bahr, J; Ban, J; Baranov, P; Barrelet, E; et al. (1999)
Interactions of the type ep → eXY are studied, where the component X of the hadronic final state contains two jets and is well separated in rapidity from a leading baryonic system Y. Analyses are performed of both resolved and direct photoproduction and of deep-inelastic scattering with photon virtualities in the range 7.5 < Q2 < 80 GeV2. Cross sections are presented where Y has mass MY < 1.6 GeV, the squared four-momentum transferred at the proton vertex satisfies \t\ < 1 GeV2 and the two jets each have transverse momentum pjetT > 5 GeV relative to the photon direction in the rest frame of X. Models based on a factorisable diffractive exchange with a gluon dominated structure, evolved to a scale set by the transverse momentum p̂T of the outgoing partons from the hard interaction, give good descriptions of the data. Exclusive qq̄ production, as calculated in perturbative QCD using the squared proton gluon density, represents at most a small fraction of the measured cross section. The compatibility of the data with a breaking of diffractive factorisation due to spectator interactions in resolved photoproduction is investigated.